Business accounting 2 - Wood, Frank (London : Pitman, 1984)
This is the second volume of the textbook. It completes the coverage for examinations such as the professional foundation examinations: London Chamber of Commerce Intermediate and Higher Stages, Royal Society of Arts Stage II and most of Stage III, and for the Financial Accounting part of the syllabuses for the General Certificate of Education Advanced Level.
Includes index.
ne 31/07/2019
Loans
Keywords: Accounting